The Quest for Freedom in Tennessee Williams’ The Rose Tattoo and Sweet Bird of Youth - Dewi, Novita (Universitas Sanata Dharma, 2016)
This paper examines the interface of economic hardship, sexual repression, and fear of aging in Tennessee Williams’ plays of the 1950s. Set in modern capitalist society of America, The Rose Tattoo (1955) and Sweet Bird of Youth (1959) depict the characters who are thwarted in their search for freedom that can be equated with the celebration of material prosperity and eternal youth. Using Eric Fromm’s view of freedom-as-frightful in modern society, the discussion will reveal the entrapment of self-deception in the characters’ unrealistic hope to stay young and productive in a commercialised society where sex is a commodity.